Ligand Control of the Cobalt-Catalysed 1,4-Hydrovinylation Reaction - Arndt, Marion; Dindaroğlu, Mehmet; Schmalz, Hans-Günther; Hilt, Gerhard (Synthesis, 2012)
The application of cobalt catalysts to the hydrovinylation of unsymmetrical alkenes and 1,3-dienes was investigated using modular phosphine-phosphite ligands to evaluate the influence of the ligands on the regioselectivity of the reaction. While a ligand with a TADDOL subunit (SchmalzPhos) gave the best results for the β-4 regioisomer, the corresponding BINOL-derived ligand gave predominantly the β-1 regioisomer. The application of (E)-2-methylpenta-1,3-diene in combination with the (nonracemic) BINOL-derived ligand generated the β-4 regioisomer in excellent yields and very high regioselectivities for a number of terminal alkenes bearing various functional groups. In one case, the enantiomeric excess of a chiral product, i.e. a 3,5-dimethylhexa-1,4-diene derivative, was determined by chiral RP-HPLC to be 78% ee.
Keywords: alkene; catalysis; cobalt; diene; 1,4-hydrovinylation